Application of artificial intelligence in nuclear medicine and molecular imaging: a review of current status and future perspectives for clinical translation. - Visvikis, Dimitris; Lambin, Philippe; Beuschau Mauridsen, Kim; Hustinx, Roland; Lassmann, Michael; Rischpler, Christoph; Shi, Kuangyu; Pruim, Jan (European Journal of Nuclear Medicine & Molecular Imaging, 2022)
Artificial intelligence (AI) will change the face of nuclear medicine and molecular imaging as it will in everyday life. In this review, we focus on the potential applications of AI in the field, both from a physical (radiomics, underlying statistics, image reconstruction and data analysis) and a clinical (neurology, cardiology, oncology) perspective. Challenges for transferability from research to clinical practice are being discussed as is the concept of explainable AI. Finally, we focus on the fields where challenges should be set out to introduce AI in the field of nuclear medicine and molecular imaging in a reliable manner.